PEMBERIAN PUNISHMENT SEBAGAI WUJUD PEMBENTUKAN KARAKTER DISIPLIN SISWA - Agung Subakti; Sri Yanti; Purwandari, Elce; Hartatik; Ellese Sulistianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Teachers in schools nowadays face numerous challenges in shaping students' character due to the onslaught of influences from the surrounding environment, advancing technology, and media readily accessible to students. Various concepts are being attempted by teachers in schools for the progress and success of education. One of the concepts frequently employed by teachers is character education. This research aims to analyze the formation of students' disciplined character through the provision of punishment. Data collection techniques used include observation, documentation, and direct interviews with the subjects under study, namely the school principal, curriculum vice principal, and classroom teachers at SDIT Annajiyah Lubuklinggau. The data analysis technique employs triangulation. The research findings reveal that teachers are aware of character education and believe it should be provided to students. All teachers implement forms of character education for students. During the learning process, teachers administer punishment to students who violate rules. The punishment administered is educational rather than physical. Students respond positively to the punishment received. The given punishment has both positive and negative impacts on students. The positive impact can enhance students' discipline, while the negative impact can lead to decreased self-confidence, manipulative behavior, and anxiety if the punishment is not administered following principles of fairness, proportionality, and rehabilitation. Thus, the conclusion of this research is that character formation through the provision of punishment to students can enhance student discipline if carried out following principles of fairness, proportionality, and rehabilitation.